Management and Performance in the Public Sector: Evidence from German Municipalities - Florian Englmaier; Gerd Muehlheusser; Andreas Roider; Niklas Wallmeier (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study management practices and performance of public sector organizations in Germany. For a representative sample of municipalities, we provide survey evidence for substantial het-erogeneity in the use of structured management practices. This heterogeneity is not driven by differences across states, regional types, or population size. Moreover, we document a system-atic positive relationship between the degree of structured management and a diverse set of performance measures capturing municipalities' attractiveness for citizens and firms. Topic modelling (LDA) of survey responses suggests that management styles differ indeed in the extent of structured management, with many municipalities displaying relatively little of it.
Keywords: D20; D73; H11; H73; R50; 330; management practices; public sector organizations; local government; municipal performance; World Management Survey (WMS)